Pengembangan multimedia pembelajaran patiseri untuk siswa tingkat XI SMK - Tri Sunarmi; Amat Jaedun (Jurnal Pendidikan Vokasi, 2015)
Penelitian ini bertujuan untuk: 1) mengembangkan multimedia pembelajaran patiseri pada standar kompetensi mengolah kue pastry kontinental untuk siswa tingkat XI SMK yang layak dari aspek pembelajaran, materi, dan media; 2) mengetahui keefektifan multimedia pembelajaran patiseri yang dikembangan terhadap penguasaan kompetensi belajar mengolah kue pastry kontinental dilihat dari peningkatan skor tes hasil belajar. Jenis penelitian ini adalah penelitian dan pengembangan. Subyek penelitian adalah 36 siswa, untuk uji coba kelompok kecil dan uji coba lapangan. Validasi produk dilakukan oleh ahli materi dan ahli media. Selanjutnya data dianalisis dengan teknik analisis deskriptif.Hasil penilaian ahli materi dan ahli media menunjukkan bahwa kualitas multimedia "baik". Penilaian siswa pada uji coba lapangan mengenai kualitas multimedia dari aspek pembelajaran, aspek materi dan aspek media "sangat baik", dengan rerata skor dari ketiga aspek 4,49. Hasil pretes menunjukkan rerata sebesar 63,15 sedangkan rerata pada posttes sebesar 89,07. N-gain sebesar 0,72 termasuk kategori "tinggi". Kesimpulannya: multimedia pembelajaran patiseri hasil pengembangan layak dignakan untuk media pembelajaran dan efektif untuk meningkatkan hasil belajar siswa. DEVELOPING PATISSERIE TEACHING MULTIMEDIA FOR GRADE XI STUDENTS OF SMKAbstractThe research aims to: 1) develop the patisserie teaching multimedia at the standard competency for continental pastry for eleventh grade vocational students in patisserie program which is appropriate in terms of teaching aspect, material aspect, and media aspet; 2) reveal the effectiveness of the developed patisserie teaching multimedia at the standard competency forcontinental pastry, which is seen from the increase in the learning achievement test score. This research is a research and development. The subjects of the research are 36 students.The students are devided into two groups: small group trials and field trials. The data were analyzed by using the discriptive technique.The results of the product validation from the material expert and media expert show that the quality of the developed patisserie teaching multimedia is "good". The assessment of the students on the field trial of the quality of the multimedia from the teaching aspect, material aspect and media aspect get the score "very good". This shows that the quality of the developed patisserie teaching multimedia is in a "very good" category. The average score from the three aspects is 4.49 and it can be used as a patisserie teaching multimedia. The students' average score from the pretest is 63.25 while from the posttest is 89.07. Based on the pretest and posttest scores the n-gain is 0.72, and it is included in a "high category". Therefore the patisserie teaching multimedia is effective to improve the students' learning achievement.